Bentuk Pelaksanaan, Makna Simbolik dan Nilai Filosofi Pada Tradisi Kupatan Masyarakat Kabupaten Tulungagung - Millatuz Zakiyah; NawangTsany, Kamila (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2023)
In the Kupatan tradition, a common effort for blessings and prosperity is being undertaken by an entire community. This study uses qualitative method which aims to focus on implementation, the symbolic interpretation of food, and the philosophical values that exist in the Kupatan tradition. This study uses descriptive qualitative method. Meanwhile, data collection method used by researchers in the form of observation, interview techniques, and literature study. According to the results of this study, there are many symbolic meanings of food in the implementation of the kupatantradition, starting from what is categorized as the main food, namely kupat, along with the meaning of the raw material, namely white rice and its wrapping material, namely coconut leaves, as well as the symbolic meaning of various complementary foods in this tradition. Furthermore, the philosophical value is also analyzed in the form of implementing the Kupatan tradition which concludes that the implementation of the Kupatan tradition can shape the Tulungagung community in living a positive, tolerant, and harmonious social life with one another. Researchers hope that this tradition can be preserved by future generations and will be reviewed by future researchers in order to provide and find more up-to-date studies of the Kupatan tradition.